Understanding Class in the Post-Industrial Era - Thoughts on Modes of Investigation - Byrne, David S. (Frontiers in Sociology, 2020)
The essential character of social science is that is founded around an interaction between theoretical framings and empirical investigation. Class is one of the most salient framing concepts of the discipline, always central even if somewhat pushed into the background in an era when identities not founded in economic relations seemed to take priority. Recently in an era of austerity and economic crisis class is very much back front and centre. The issue addressed in this article is how can and should we investigate class in the societies in which classes emerged from industrial systems when those societies are now not only post-industrial but also to an increasing degree post-welfare in consequence of the defeat and retreat of a coherent class based politics. Traditionally there has been a distinction between studies which used primarily qualitative styles – ethnographic and at the interface of history and sociology – on the one hand and quantitative studies based on the analyses of large data sets on the other. It has to be said that many of the latter used linear modelling approaches which were of questionable value, particularly when the only dynamic element in them was the exploration of just two time points in the life course in relation to social mobility. What will be proposed here is the value not only of studies which deploy ethnographic / historical and related qualitative modes but also of quantitative work, including in particular quantitative histories, which break with the linear model and deploy dynamic modes of investigation across a range of social scales from the individual life course to the whole global social order. One central proposition in the article is that in order to grasp the nature and potential of class after industry we have to engage in meta-interpretation – that is scholarly, we might say hermeneutic, reflection on multiple studies conducted in all appropriate modes of social investigation.